Negotiating identities: Inuit tuberculosis evacuees in the 1940s-1950s - Olofsson, Ebba; Holton, Tara; Partridge, Imaapik (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractIn the mid 1940s the Canadian government implemented a medical mass-survey of Inuit and other Indigenous peoples living in northern Canada, and evacuated those suspected of having tuberculosis to hospitals in the south. Hospital stays often lasted for years at a time and while some patients were eventually returned to their home communities, many never returned, some because they chose to stay in the south and others because they did not survive their illness. The current study is interested in how hospitalisation in the south affected the identity of Inuit patients, and in particular examines the negotiation of identity as a form of resilience. This investigation is conducted through life history interviews with Inuit former evacuees in which we explore their experiences of departure, travel, and sojourn in an unfamiliar environment, as well as their lives after the hospital stay.